Boris Lissanevitch and Nepali Tourism: History Revisited - Singh Mahato, Gyaneshwor Prasad; Dahal, Anish (Journal of Tourism and Himalayan Adventures, 2021)
In the transitional phase of Nepal, attaining peoples’ democracy in the 1950, the tourism and hospitality sector witnessed dynamism. The isolated Nepal was on the way of opening for tourism. This paper tries to frame a picture of the era of 1950s in Nepal when commercial tourism was introduced. An overlooked pioneer, Boris Lissanevitch, who established the international-standard Royal Hotel in Kathmandu in 1954, assisted in making key changes in the progression of tourism as visa issuance, hospitality modernization, management of royal events, sightseeing activities, accomplishing inter-continental land cruise, and introduction of European vegetables and dishes. His vision of tourism as an economic sector led Nepal attaining its golden age (of tourism) thus paving the way for other tourism and hospitality enthusiasts to establish similar businesses. This paper aims at interpreting and appreciating the efforts Boris made in the development of tourism in Nepal among tourism scholars and stakeholders